2003
DOI: 10.1021/jp0303063
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of a Polyanion with a Cationic Micelle:  Comparison of Monte Carlo Simulations with Experiment

Abstract: Monte Carlo simulations were used to investigate the adsorption of a polyelectrolyte chain on an oppositely charged micelle. The influence of the concentration of monovalent salt on the isolated polyelectrolyte chain was investigated by considering the chain expansion factor and persistence length. The polyelectrolytemicelle complex was characterized in terms of the amount of adsorbed polymer in trains, loops, and tails. The overcharging of the complex and the conformation of the adsorbed polyelectrolyte chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…A similar approach was employed in a recent study of complexation of a polyanion with a cationic micelle. 52 While the curves for the systems with monovalent ions (DCI-111 and DCI-121) remain almost unchanged compared to those in Figure 6 (top), one can witness a noticeable overcharging for a dendrimer in the presence of divalent ions at λ B g 3.0l 0 . This result contrasts with the findings of a recent simulation study by Majtyka and Klos, 27 who studied single charged dendrimers under the presence of mono-and divalent salt and did not observe overcharging of dendrimers for a wide range of the Bjerrum lengths.…”
Section: B Counterion Condensation and Chain Dehydrationmentioning
confidence: 84%
“…A similar approach was employed in a recent study of complexation of a polyanion with a cationic micelle. 52 While the curves for the systems with monovalent ions (DCI-111 and DCI-121) remain almost unchanged compared to those in Figure 6 (top), one can witness a noticeable overcharging for a dendrimer in the presence of divalent ions at λ B g 3.0l 0 . This result contrasts with the findings of a recent simulation study by Majtyka and Klos, 27 who studied single charged dendrimers under the presence of mono-and divalent salt and did not observe overcharging of dendrimers for a wide range of the Bjerrum lengths.…”
Section: B Counterion Condensation and Chain Dehydrationmentioning
confidence: 84%
“…[16][17][18][19][20][21][22][23][24][25] The magnitude of the electrostatic interaction between the polyelectrolyte and the oppositely charged colloid is found to increase with colloid surface charge density σ and polyelectrolyte linear charge density and diminish with salt concentration I. One way to express a consensus among the numerous experimental investigations and their theoretical or simulation counterparts would thus be 26 where σ c is the critical colloid surface charge density at the onset of complex formation and κ is the DebyeHuckel parameter, with a and b being either obtained as empirical scaling parameters or derived theoretically. Comparison between theory and experiment is of course complicated by structural features of colloid and polymer, ignored in theory.…”
Section: Introductionmentioning
confidence: 99%
“…workers 26,33 have indicated that desorption of an oppositely charged spherical particle from a polyelectrolyte chain occurs at a critical salt concentration, which varies inversely with L p . In brief, all these studies have pointed out that flexible, i.e., low L p , polyelectrolyte chains bind more strongly to oppositely charged colloids than stiffer chains do.…”
Section: Introductionmentioning
confidence: 99%
“…There is nowadays a considerable amount of available contributions investigating the PE/macroion complexation by [24][25][26][33][34][35][36]. The effect of chain stiffness of a strong PE were first studied by Wallin and Linse [22] and then further investigated by Stoll and Chodanowski [26] and Akinchina and Linse [27].…”
Section: Simulationsmentioning
confidence: 99%